Pressure-swing distillation process for separating ternary azeotropic mixture of acidic aqueous solution. Issue 7 (3rd July 2022) - Mahida, B.; Benyounes, H.; Jin, S.; Shen, W.
Abstract: The separation of ternary mixture of acidic aqueous solution is difficult due to presence of both binary and ternary azeotropes that generate distillation boundaries. In this work, a pressure-swing distillation process for separating the mixture was investigated. Three variants of pressure swing distillation process were therefore proposed. The operating pressure of each distillation column was chosen on the basis of the location of the feed composition in the distillation regions. The sensitivity analysis of the operating parameters of each separation process was carried out to determine the best operating conditions to reach higher purity for the three products (i.e., 99.9 mol.%). It has been found that formic acid and water present in the ternary mixture with high content can be separated twice as a distillate product with total molar recovery ratio of about 90%. In addition, the energy consumed to separate water was higher than that required to recover formic acid.